SYNTHESIS OF SOME SUBSTITUTED NAPHTHALENES VIA BENZYNE AND THEIR 13C-NMR AND 'H-NMR STUDIES (Journal of Sciences, Islamic Republic of Iran)
Aprotic diazotization of anthranilic acid with isoamylnitrite or amylnitrite gave benzenediazonium-2- carboxylate. Subsequent thermal decomposition of this diazonium salt (in situ) in 1,2-dichloroethane as a solvent at 85OC and in the presence of 2,5-diethyl-3,4-diphenylcyclopentadienonaes a trapping agent gave 1,4-diethyl-2, 3-diphenylnaphthalene in high yield, after loss of carbon monoxide. Also, thermal decomposition of this diazonium salt (in situ) was carried out in 1,1 ,2-trichloroethane as a solvent at 108OC in the presence of 2,5-dimethyl-3,4-diphenylcyclopentadienone (monomer) and after loss of carbon monoxide, 1,4-dimethyl- 2,3-diphenylnaphthalene was obtained in excellent yield. These naphthalene derivatives were studied by IR, 'H-NMR, 13C-NMR mass spectra and elemental analysis